The effects of problem based learning on reading aloud strategies for Pakistani medical students' reading comprehension in genetics & molecular biology - Sajid, Muhammad Khalid Mehmood; Hafizoah, Kassim; Iqbal, Zafar; Aljarrah, Khaled; Hasan, Ghasan Adnan; Al Anazi, Nawaf (Solid State Technology, 2020)
Problem-based learning techniques build up cognitive skills in the students of Medical Science. Nowadays, students are facing difficulties in different language skills, particularly in reading. Read aloud strategies help in literacy development and for reading successfully. Reading plays a significant role in knowledge development and enhances confidence in students and improves their reading comprehension. Problem-based learning is an important method that can solve students learning problem-related to medical study. This study is an attempt to know the effects of problem-based learning in reading aloud strategies. The study aimed to know the impact of Problem-based learning techniques that how they helped reading aloud strategies, and how it could make medical-related learning more effective for adequate reading comprehension. In this study, data was collected from a Pakistani Medical College, for which convenience sampling was used. A survey questionnaire and interviews were used for a sample size of 40 students. Further, all the available teachers were also interviewed. A mixed methodology was used. SPSS was used for quantitative data analysis. ATLAS ti 8 was used as a qualitative software for excerpts analysis from the interviews. The findings showed a reasonable effect of Problem-based learning for effective reading aloud strategies used by medical college students for reading comprehension improvement.